[Marcopper ; Boracay ; Saguisag [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
A group of concerned citizens charge the copper mining company of dumping its mining waste into the bay causing polluted water and loss of livelihood for the fisherfolk. A look at changes in Boracay Island. Profile of senator Rene Saguisag.